PRODUCT INNOVATION STRATEGY IN MEDIATING THE EFFECT OF ETHICAL BEHAVIOUR AND ETHICAL RESPONSIBILITY AND TRUST ON MARKETING PERFORMANCE - Lustono; Wening, Nur (Universitas Teknologi Yogyakarta, 2020)
This study aims to determine: the influence of Ethical Behaviors and Ethical Responsibility and Trust on marketing performance. The effect of Ethical Behaviors and Ethical Responsibility and Trust on product innovation. Effect of Product Innovation on marketing performance. The effect of Ethical Behaviors and Ethical Responsibility and Trust on marketing performance through product innovation.This type of research is quantitative research, with research variables Ethical Behaviors, Ethical Responsibility And Trust, product innovation and marketing performance. The population in this study is consumers of Yamaha N 'Max motorcycle products in Banjarnegara Regency. The sampling method is purposive sampling, based on characteristics or criteria,n and the number of samples is 100 respondents. The data collection method uses a questionnaire. The analysis technique used is multiple linear regression equations with a significance level of 5%.The results shows that Ethical Behaviors have a positive and not significant effect on marketing performance. Ethical Behaviors have a positive and insignificant effect on product innovation. Ethical Responsibility and Trust and product innovation have a positive and significant impact on marketing performance. Product innovation is able to mediate the influence of Ethical Behaviors. Product innovation is able to mediate the influence of Ethical Responsibility and Trust on marketing performance.